STUDYING THE EXPERIENCE OF APPLICATION OF NON-INVASIVE METHODS TO ASSESS THE FUNCTIONAL STATE OF THE ORGANISM UNDER PHYSICAL AND PSYCHOEMOTIONAL LOADS - Zhaldak, Anastasiia; Ivanko, Olesia; Deputat, Yurii (The Ukrainian Scientific Medical Youth Journal, 2021)
In the literature review considered of professional work of servicemen of Special Operations Forces of Armed Forces of Ukraine with accent on qualification course of Special Operations Forces have been reviewed. Based on available scientific reports, mechanisms of adaptive reactions of organism to physical and mental loads have been summarized. The literature data on the organism reactions to physical and psycho-emotional stress are summarized. It was pointed out that the result of primary metabolic response of organism for extreme physical loads and stress is activation of free radical oxidation of membranes’ lipids. Biological marker of this process activation may be polysaturated fatty acids and their qualitative and quantitative changes in biological fluids characterize functional state of organism during physical and mental loads.Systemization of literature sources and approaches to solve problem of use of noninvasive analysis of biological fluids indicated that based on biochemical analysis of biological fluids there is an opportunity to reveal the level of activation of lipid peroxidation i.e. adaptive reactions of organism.